2006
DOI: 10.1155/2006/90279
|View full text |Cite
|
Sign up to set email alerts
|

Laser Cleaning of Easel Paintings: An Overview

Abstract: The application of laser cleaning to paintings is relatively recent despite its use on stone-based materials for over 30 years. The cleaning of paintings is of high importance, because it is the least reversible invasive intervention, as well as the most usual of all conservation treatments. Paintings are multilayer system of heterogeneous nature, often very sensitive and inherent difficult to clean. Being a noncontact method, laser cleaning has advantages compared to alternative techniques. Over the last deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…As attested by previous studies, plattnerite has a very weak Raman scattering, and it can degrade if the excitation laser power is not kept sufficiently low . The problem of laser‐induced degradation of lead pigments is indeed a well‐known phenomenon, even if some aspects still have to be better understood . It has been repeatedly shown that if the laser power is higher than some threshold, depending on the laser wavelength and the nature of the analysed sample, degradation phenomena may be triggered during Raman analyses and secondary products, such as red lead, massicot and litharge, are formed .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As attested by previous studies, plattnerite has a very weak Raman scattering, and it can degrade if the excitation laser power is not kept sufficiently low . The problem of laser‐induced degradation of lead pigments is indeed a well‐known phenomenon, even if some aspects still have to be better understood . It has been repeatedly shown that if the laser power is higher than some threshold, depending on the laser wavelength and the nature of the analysed sample, degradation phenomena may be triggered during Raman analyses and secondary products, such as red lead, massicot and litharge, are formed .…”
Section: Resultsmentioning
confidence: 92%
“…[45] The problem of laser-induced degradation of lead pigments is indeed a well-known phenomenon, even if some aspects still have to be better understood. [46,47] It has been repeatedly shown that if the laser power is higher than some threshold, depending on the laser wavelength and the nature of the analysed sample, degradation phenomena may be triggered during Raman analyses and secondary products, such as red lead, massicot and litharge, are formed. [48][49][50] Thus, we decided to perform first Raman measurements on plattnerite standards, both on mineral plattnerite and on powdered synthetic plattnerite (with excitation laser at 633 and 532 nm), to choose the suitable analysis parameters and to avoid any thermal degradations on the real mural painting samples.…”
Section: Analysis Of Plattnerite Standardsmentioning
confidence: 99%
“…The use of lasers in cleaning the objects of cultural heritage in recent years has become a standard method in conservation due to the fact that laser is highly controllable and can remove the surface contaminants precisely and selectively [8][9][10]. The application of laser in cleaning stone is described in paper [8], marble in [10], glass [11,12], ceramics [13,14,15], wall painting [16], pictures on canvas and wood [17], metal objects [9,[18][19][20], textile [21][22][23][24], other organic and biological samples [17] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The Conservation's Laboratory of NGA provided to the National Technical University of Athens (NTUA) three small pieces from the two out of three burnt paintings, in order to identify the existing pigments after the fire. The aim is to investigate and suggest the optimum cleaning methodology, based on laser cleaning, a very promising cleaning method [1] [2] .…”
Section: Introductionmentioning
confidence: 99%